Effect of B. Monnieri Leaf Extract Targeted at Adenosine Receptor in Diabetic Neuropathic Pain - P K SAHOO; D PRADHAN; P BEHERA (International Journal of Pharma and Bio Sciences, 2010)
Diabetic neuropathic pain is generally considered to be one of the most troublesome complications affecting diabetic patients and current therapy provides inadequate pain relief. In the present study, the neuroprotective effect of Bacopa monnieri, Linn. (Brahmi, BM) targeted at adenosine receptor was studied in a model of diabetic neuropathic pain. Diabetes was induced by streptozotocin (65 mg/kg, ip) in male Sprague Dawley rats and subjected to thermal (cold and hot) and chemical (formalin) stimuli. Diabetic rats developed hyperalgesia by the end of six weeks in thermal and chemical stimuli test. Ethanolic extract of Bacopa monnieri leaf (EEBM) (500 mg/kg, ip) produced significant reversal of responses to thermal and chemical stimuli in diabetic rats. The results indicate that EEBM is an effective analgesic in a model of diabetic neuropathy, and the protection produced by EEBM is via stimulation of adenosine A1-receptors.